The Importance of Invigilator Training - deMontigny, David (Canadian Perspectives on Academic Integrity, 2023)
Graduate students are often hired to help faculty members invigilate examinations. However, without proper training and support, how can the institution be sure the invigilators they hired are prepared to approach someone who may be cheating? Additionally, has the institution told invigilators how to report allegations of misconduct to the appropriate investigation body? This presentation will highlight the importance of training invigilators so they are properly prepared to serve in this important role. The presenter will discuss the rights of the individual writing the exam and the rights of the invigilator(s). The discussion will include advice on how prepare individuals to be a successful invigilator. Real examples of what can happen during an exam, both good and bad, will be shared.